All-optical half-subtractor with low-time delay based on two-dimensional photonic crystals. (September 2017) - Parandin, Fariborz; Malmir, Mohammad-Reza; Naseri, Mosayeb
Abstract: In order to rapidly process information, high-speed processors are required. Optical instruments are appropriate for optical processors because of the high speed of information transference. In order to design optical processors, a structure that has the ability to integrate is required. Photonic crystals are suitable structures that can be used to design and implement different kinds of optical instruments. In this paper, an optical half-subtractor has been designed, based on two-dimensional photonic crystals. Owing to its small size and simple design, this half-subtractor can be used in optical integrated circuits. The very low-time delay of this half-subtractor is responsible for its high bit-rate. Highlights: Optical logic gates are a suitable basis for design of optical integrated circuits. In this study, All-Optical Half-Subtractor Based on Two-Dimensional Photonic Crystals was designed. The proposed Half-Subtractor has a small size, low time delay and then high bit rate.